Coercion in Gendered Power Relations in Caryl Churchill’s Vinegar Tom - Dlshad Mohammed Amin , Lona; Zainalddin Mohammed , Rebwar (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This paper titled “Coercion in Gendered Power Relations in Caryl Churchill’s Vinegar Tom” examines the coercive gendered relations of power in the play. Gender is an effective form of social power and gender norms occur within a binary system that can often be restrictive and coercive, compelling subjects to conform to them to prove their illegibility to belong to what is considered normal or human. The reason for choosing this play is that it is often recognised as one of Churchill’s best feminist works in which she addresses gender issues and the struggles arising from not conforming to the norms governing one’s assigned gender. It is set in the seventeenth century and deals with gender issues from different angles where the struggles of women in the past are portrayed and linked to the struggles of women in today’s world.